Aqueous Extract of Solanum nigrum Leaves Induces Autophagy and Enhances Cytotoxicity of Cisplatin, Doxorubicin, Docetaxel, and 5-Fluorouracil in Human Colorectal Carcinoma Cells. (17th June 2013) - Tai, Chen-Jei; Wang, Chien-Kai; Tai, Cheng-Jeng; Lin, Yi-Feng; Lin, Chi-Shian; Jian, Jiun-Yu; Chang, Yu-Jia; Chang, Chun-Chao
Abstract : Colorectal cancer is a common cancer worldwide, and chemotherapy is a mainstream approach for advanced and recurrent cases. Development of effective complementary drugs could help improve tumor suppression efficiency and control adverse effects from chemotherapy. The aqueous extract of Solanum nigrum leaves (AE-SN) is an essential component in many traditional Chinese medicine formulas for treating cancer, but there is a lack of evidence verifying its tumor suppression efficacy in colorectal cancer. The purpose of this study is to evaluate the tumor suppression efficacy of AE-SN using DLD-1 and HT-29 human colorectal carcinoma cells and examine the combined drug effect when combined with the chemotherapeutic drugs cisplatin, doxorubicin, docetaxel, and 5-fluorouracil. The results indicated that AE-SN induced autophagy via microtubule-associated protein 1 light chain 3 A/B II accumulation but not caspase-3-dependent apoptosis in both cell lines. The IC50 s after 48 hours of treatment were 0.541 and 0.948 mg/ml AE-SN in DLD-1 and HT-29, respectively. AE-SN also demonstrated a combined drug effect with all tested drugs by enhancing cytotoxicity in tumor cells. Our results suggest that AE-SN has potential in the development of complementary chemotherapy for colorectal cancer.